The networks of care surrounding cancer palliative care patients - Jarrett, Nikki; Porter, K.; Davis, C.; Addington-Hall, J.; Duke, S.; Corner, Jessica; Lathlean, J. (BMJ Publishing Group, 2015)
Objectives: This paper explicates the nature and extent of the networks of care surrounding patients with cancer palliative care needs.